การกำจัดไนโตรเจนและฟอสฟอรัสในระบบหมุนเวียนน้ำเพื่อการเลี้ยงสัตว์น้ำด้วยถังบรรจุเม็ดดินเผาและผักกวางตุ้ง - เอกนรินทร์ ธนะกิจไพรินท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research evaluated the nitrogen and phosphorus removal efficiency in the recirculating aquaculture system (RAS) with the water treatment tank containing plant and baked clay beads. The experiments consisted of 3 parts i.e., (1) the study on suspended solid accumulation during fish culture at low (0.5 kg/m³) and high (2 kg/m³) densities, (2) estimation of nitrogen and phosphorus content in Chinese cabbage (Brassica pekinensis), and (3) evaluation of the RAS for fish (Nile tilapia: Oreochromis niloticus) cultivation with water treatment using baked clay beads for sediment removal and Chinese cabbage for nutrients removal. The results showed that high density culture of tilapia produced high amount of suspended solids and this solids commencing on nitrification treatment of nitrogen wastes (ammonia and nitrite). Removal of suspended organic solid from the RAS at 50% for 6 rounds revealed that an increase of suspended solid (SS) to the original concentration took approximately 4 days and the SS removal rates were 2.45±0.73 and 5.17±1.26 mg/L-day for low and high density fish culture, respectively. Growth comparison between Chinese cabbage cultivated in baked clay beads and organic soil for 45 days showed that organic soil provided higher growth rate (0.04±0.01 g-wet/tree-day) than in baked clay beads (0.03±0.01 g-wet/tree-day) with nitrogen and phosphorus content was 100 and 1.78%, respectively. In the last experiment, the water from Nile tilapia tank was circulated to the baked clay beads tank containing Chinese cabbage at 3 L/min for the continuous cycle of 10 minutes flow and 60 minutes pause. Three experimental units were assigned as treatment (fish tank + baked clay beads tank with Chinese cabbage), control-1 (fish tank only), and control-2 (fish tank + baked clay beads tank without Chinese cabbage). It was found that growth of tilapia in treatment tanks (0.45±0.15 g-wet/day) was higher than control-1 and control-2 tanks (0.37±0.16 and 0.38±0.05 g-wet/day, respectively). Average weight of Chinese cabbage increased from 0.15±0.02 to 1.00±0.38 g-wet. Water quality analysis revealed that water quality in treatment tank had lower ammonia, nitrite nitrate and phosphate concentration than control systems. However, nitrogen and phosphorus balance analysis showed that only 1.31% of nitrogen and 0.11% of phosphorus input was incorporated into Chinese cabbage. Hence, nitrogen and phosphorus removal by plant was only the minor role. Most of the nitrogen removal was from decomposition and denitrification processes in sediment layer trapped in baked clay beads tank.